Communication and Mobility: Mobile-Mediated Displacement Experiences in Buenos Aires - Durr Missau, Lucas (2021)
This article aims to identify and describe the specificities of the urban mobility experience of inhabitants who use transportation apps to move around the city of Buenos Aires taking into account social, economic and cultural aspects of their experiences. We seek elements to understand how the use of these apps is part of people’s daily lives and, ultimately, to what extent it contributes to social inclusion, revealing the social aspects that are at stake. Intending to mobilize communication studies, theoretically, this paper articulates the new paradigm of mobilities in the social sciences with cultural studies. We accompanied nine participants of the study, from the first event of their days to the last, during a daily journey. When accompanying them around the city, the collection instruments included interviews and video recording of travel moments from the perspective of the participants themselves, who wore glasses with a hidden video camera. Based on the narratives of participants’ life stories during commuting, we describe how imagining, adapting and belonging to a strange and at times hostile environment relates to mobile-mediated travel experiences. Therefore, we describe processes in which the narratives about the experiences of migration and the daily flows of displacement are articulated with the mediation of transportation applications.